2000
DOI: 10.2214/ajr.174.4.1740915
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Subsecond Gated Helical CT for Quantification of Coronary Artery Calcium and Comparison with Electron Beam CT

Abstract: A general purpose, current generation helical CT scanner equipped for retrospective cardiac gating can accurately quantify coronary calcium, and the results are highly correlated to scores obtained with electron beam CT. As an alternative method for measuring coronary calcium, gated subsecond cardiac helical CT offers greater availability and lower cost, thereby making population-based screening for coronary artery calcium more feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
124
0
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 227 publications
(130 citation statements)
references
References 28 publications
1
124
0
4
Order By: Relevance
“…Two trained readers blinded to the clinical characteristics of the participants analysed the CT images. As previously reported, helical CT scans yield comparable vascular calcium measurements to electron beam CT [36]. The cardiac CT methods that we used in the DHS replicate those employed in the Multi-Ethnic Study of Atherosclerosis (MESA) and Coronary Artery Risk Development In Young Adults studies [37].…”
Section: Vascular Imagingmentioning
confidence: 62%
“…Two trained readers blinded to the clinical characteristics of the participants analysed the CT images. As previously reported, helical CT scans yield comparable vascular calcium measurements to electron beam CT [36]. The cardiac CT methods that we used in the DHS replicate those employed in the Multi-Ethnic Study of Atherosclerosis (MESA) and Coronary Artery Risk Development In Young Adults studies [37].…”
Section: Vascular Imagingmentioning
confidence: 62%
“…22 Multidetector CT (MDCT) scanners have evolved to the point that cardiac image acquisition is comparable to that of electron beam CT scanners. Studies have showed CAC detection equivalency between electron beam CT and multislice CT. 23,24 With MDCT, accurate CAC detection is now widely available to EDs across the United States. Detection of CAC by CT is noninvasive, easily tolerated, and rapid, and it requires no intravenous contrast medium.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore CAC scores are mostly assessed today using MDCT. Others have suggested that the thresholds derived from EBCT technology may not be readily transferred to newer CT scanners [9,23,24,26,32]. Our results show that systematic differences in CAC scores due to different scanner types cause only a few misclassifications of CACderived risk group categories, and adjustment according to the systematic bias did not lead to a significant improvement in risk group classification.…”
Section: Discussionmentioning
confidence: 49%
“…They found EBCT and MDCT to be highly correlated (correlation coefficient between 0.95-0.99). However, newer scanner generations implicate a systematic difference in scoring due to differences in temporal and spatial resolution, image noise and lack of calibration [7,26], resulting in a variation from 17% to 32% in CAC scores compared with EBCT [8,9,[23][24][25]. Our results also showed a high correlation of r50.971 and a standard variation of 14% in CAC scores.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation